Measuring quality and level of care provided by family caregivers of persons with dementia: protocol for a systematic review of validated instruments - Afeez Abiola Hazzan; Joyce O Hazzan; Mark Oremus (AIMS Press, 2021)
Background: Changes in the quality-of-life (QoL) of family caregivers as they care for their loved ones with dementia over time may affect the quality or level of care that these caregivers provide. We do not know if validated instruments exist to directly measure this quality or level of care. The purpose of this systematic review is to identify validated instruments for measuring the quality or level of care provided by family caregivers of persons with dementia. Methods: We will include articles containing a validated instrument or questionnaire designed to measure quality or level of care provided by the aforementioned group of caregivers. The included articles may utilize the tools in primary or secondary data analyses, or evaluate the tools' psychometric properties. The following electronic databases will be searched from inception date to the present: Medline, CINAHL Complete, Cochrane Central, and PsycINFO. We will also search the gray literature, the reference lists of included articles, and contact experts in the field to help identify relevant instruments. Included articles will be required to report on an instrument measuring at least one of the following outcomes: quality of care, level of care, appropriateness of care, amount of time spent providing care, and caregiver performance. Two reviewers will independently screen retrieved citations, extract data, and assess the methodological quality of each included article. A narrative synthesis method will be used to describe the findings. Discussion: Results of this systematic review will show whether validated instruments exist to measure the quality or level of care provided by family caregivers of persons living with dementia. This will make it possible to develop initiatives that are targeted towards improving the quality or level of care provided by family caregivers.